Systems analysis and project management - Cleland, David I.; King, William Richard (New York : McGraw-Hill, 1968)
This book is an attempt to present the modern ideas of systems analysis and project management in a form which will demonstrate their essential unity and their applicability in a wide variety of industrial and governmental management environments.
Includes bibliographical references and index.
hza 02/08/2018
Loans
Keywords: System analysis; Project management